Effects of Virtual Care and Same-Day Access to Integrated Care on Specialty Mental Health Engagement in the Veterans Health Administration - Taona P. Haderlein; Aram Dobalian; Pushpa V. Raja; Claudia Der-Martirosian (Journal of Primary Care & Community Health, 2023)
Background: In the Veterans Health Administration (VA), Primary Care-Mental Health Integration (PC-MHI) clinics offer mental health services embedded in primary care, a strategy shown to reduce overall specialty mental health clinic burden while facilitating prompt referrals when indicated. Among newly initiated patients, same-day access to PC-MHI from primary care increases subsequent specialty mental health engagement. However, the impact of virtual care on the association between same-day access to PC-MHI and subsequent mental health engagement remains unclear. Objective: To examine the effects of same-day access to PC-MHI and virtual care use on specialty mental health engagement. Methods: We used administrative data from 3066 veterans who initiated mental health care at a large, California VA PC-MHI clinic during 3/1/2018 to 2/28/2022 and had no previous mental health visits for at least 2 years prior to the index appointment. We conducted Poisson regression analyses to examine the effects of same-day access to PC-MHI, virtual access to PC-MHI and their combined effect on subsequent specialty mental health engagement. Results: Same-day access to PC-MHI from primary care was positively associated with specialty mental health engagement (IRR = 1.19; 95% CI 1.14-1.24). Virtual access to PC-MHI was negatively associated with specialty mental health engagement (IRR = 0.83; 95% CI 0.79-0.87). The positive effect of same-day access on specialty mental health engagement was smaller among patients who initiated PC-MHI in a virtual visit (IRR = 1.07) compared to in-person visits (IRR = 1.29; 95% CI 1.22-1.36). Conclusions: Although same-day access to PC-MHI increased overall specialty mental health engagement, the magnitude of this effect varied between in-person and virtual modalities. More research is needed to understand mechanisms of the association between virtual care use, same-day access to PC-MHI, and specialty mental health engagement.